Evolution of Variable Number Tandem Repeats and Its Relationship with Genomic Diversity in Salmonella Typhimurium - Fu, Songzhe; Octavia, Sophie; Wang, Qinning; Tanaka, Mark M.; Tay, Chin Yen; Sintchenko, Vitali; Lan, Ruiting (Frontiers in Microbiology, 2016)
Salmonella enterica serovar Typhimurium is the most common Salmonella serovar causing human infections in Australia and many other countries. A total of 12,112 S. Typhimurium isolates from New South Wales were analyzed by multi-locus variable number of tandem repeat (VNTR) analysis (MLVA) using five VNTRs from 2007 to 2014. We found that mid ranges of repeat units of 8 to 14 in VNTR locus STTR5, 6 to 13 in STTR6 and 9 to 12 in STTR10 were always predominant in the population (>50%). in vitro passaging experiments using MLVA type carrying extreme length alleles found that the majority of long length alleles mutated to short ones and short length alleles mutated to longer ones. Both data suggest directional mutability of VNTRs towards mid-range repeats. Sequencing of 28 isolates from a newly emerged MLVA type and its five single locus variants revealed that single nucleotide variation between isolates with up to two MLVA differences ranged from 0 to 12 SNPs. However there is no linear relationship between SNP and VNTR differences. A population genetic model of the joint distribution of VNTRs and SNPs variations was used to estimate the mutation rates of the two markers, yielding a ratio of 1 VNTR change to 6.9 SNP changes. When only one VNTR repeat difference was considered , the majority of pairwise SNP difference between isolates were 4 SNPs or fewer. Based on this observation and our previous findings of SNP differences of outbreak isolates, we suggest that investigation of S. Typhimurium community outbreaks should include cases of 1 repeat difference to increase sensitivity. This study offers new insights into the short-term VNTR evolution of S. Typhimurium and its application for epidemiological typing.